(untitled) (Raparin Journal of Humanities (RJH), 2025)
The research aimed to determine the effect of using the Driver model on the achievement of third-grade students in the Kurdish language department in the subject of modern critical theories and to develop their motivation to learn the subject. The researchers adopted a quasi-experimental design with two equal groups with pre- and post-tests. An experimental group studied according to Driver‌s model and a control group studied according to the usual method. The researchers randomly selected two groups from the three sections in the third stage, and the two sections were distributed in the same manner, so the group represented Group A, which had 40 male and female students, represented the experimental group, while Group C, which had 43 male and female students, represented the control group, and parity was conducted between the two groups in several variables. The two researchers prepared an achievement test that included (40) multiple-choice and specific-answer items, as well as a scale to measure motivation to learn the subject, which included (34) items, and they extracted psychometric properties for them. After completing the experiment that began from (1/2/2024) to (4/7/2024), applying the test and scale, and conducting statistical treatment of the data using the T-test for two independent samples, The results showed that there were statistical differences at the level of (0.05) between the average achievement scores of students in the experimental and control groups, as well as development differences in the motivation scores to learn the subject, in favor of the experimental group. The researchers reached general conclusions and presented recommendations and proposals for conducting similar research in this field in the future.